The long run performance of Malaysia initial public offerings (IPOs) in construction and industrial products sector: Growth and value effects / Adeela Othman - Othman, Adeela (2007)
This project paper about the long run performance of Malaysian Initial Public Offerings (IPO) between two industries by using 30 selected companies listed at main board KLSE and period used between year 2000 to 2006. The comparisons are made to study the IPO performance after issue in public between industrial product companies and construction companies. The purpose of this study is wanted to investigate whether the growth and value effect on IPO performance in the listed companies in Malaysia. By using Cumulative Adjusted Return method, the overall result provides evidence consistent with the previous study about the long run performance of IPO. The growth and value IPO will determine depends on the Price-book value ratio (P/BV), Price earning ratio (P/E) and Price-Cash flows ratio (P/CF). This is to known whether investing in growth or value which better or outperformed after issued IPO in companies. The performance of Malaysian IPO issued by constructions companies and industrial product indicates that in the long run performance of IPO. By using independent sample test in order to test the performance of which construction companies or industrial product companies perform better in market. Shows that, there is not significantly difference. Refers to this mean shows that the industrial product companies perform better than construction companies.